Review of the potential health effects of light and environmental exposures in underground workplaces. (February 2019) - Nang, Ei Ei Khaing; Abuduxike, Gulifeiya; Posadzki, Pawel; Divakar, Ushashree; Visvalingam, Nanthini; Nazeha, Nuraini; Dunleavy, Gerard; Christopoulos, George I.; Soh, Chee-Kiong; Jarbrink, Krister; Soljak, Michael; Car, Josip
Highlights: Studies investigating health effects of underground workplaces are limited. A few adverse health effects were reported but overall findings were inconclusive. Hypothetical health effects/exposures are ample, complex and often overlap. More studies will help understanding the impact of underground spaces on health. Abstract: Underground workplaces are an important element in modern urban planning. As a result, an increasing but unquantified proportion of the population is being regularly exposed to them. We narratively reviewed the literature on the range of possible environmental exposures, and the possible health effects, to identify future research directions. There is a large but mainly observational research literature on likely underground exposures, including effects of artificial lighting, shift working and light at night on circadian disruptions and associated health effects. There are five studies comparing underground and aboveground environments. Shift working, artificial lighting and poor sleep quality leading to circadian disruption is one physiologic pathway. Working underground may increase exposure to these risks, and may also be associated with vitamin D deficiency, sick building syndrome, excessive noise, radon exposure, and negative psychological effects. In order to plan appropriate interventions, we need to expand our knowledge of the health effects of underground environments. Larger and longer-term studies are required to measure a range of human factors, environmental exposures and confounders. Controlled trials with health economic analyses of new lighting technologies are also required.